Health, social equity and changing production patterns in Latin America and the Caribbean - PAHO (PAHO WashingtonUS, 1998)
Describes a joint proposal made by ECLAC and PAHO to improve health conditions and services in Latin America and the Caribbean. Examines the relationship that exists between health and human development in Latin America and the Caribbean.